A new monohydrated molecular salt of GABA with l-tartaric acid: the structure-forming role of water. Issue 35 (9th August 2021) - Losev, E. A.; Pishchur, D. P.; Boldyreva, E. V.
Abstract : A novel monohydrated molecular salt of GABA with l -tartaric acid was crystallized and investigated. Abstract : A new hydrated molecular salt of GABA was crystallized, and its crystal structure was solved. This is the first example of a hydrated molecular salt of an achiral amino acid with l -tartaric acid and also the first communication on a hydrated molecular salt of GABA with a chiral molecule. The structure contains molecular bi-layers of l -tartaric acid anions connected together by R44(12) motifs based on GABA cations and water molecules. The role of water in the 3D hydrogen bonded network was analyzed. Structural similarity between the monohydrates of GABA with l -tartaric and orotic acid was found. We can suppose that the general R44(12) motif including 2 GABA cations and 2 water molecules would be common for other hydrated molecular salts of GABA with other co-formers, which will be obtained in the future. The stability on storage, thermal behavior and dehydration process for the novel molecular compound were investigated.